2014
DOI: 10.1093/europace/euu012
|View full text |Cite
|
Sign up to set email alerts
|

Costs of remote monitoring vs. ambulatory follow-ups of implanted cardioverter defibrillators in the randomized ECOST study

Abstract: AimsThe Effectiveness and Cost of ICD follow-up Schedule with Telecardiology (ECOST) trial evaluated prospectively the economic impact of long-term remote monitoring (RM) of implantable cardioverter defibrillators (ICDs).Methods and resultsThe analysis included 310 patients randomly assigned to RM (active group) vs. ambulatory follow-ups (control group). Patients in the active group were seen once a year unless the system reported an event mandating an ambulatory visit, while patients in the control group were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 20 publications
3
85
0
4
Order By: Relevance
“…This, however, has been achieved at the expense of an increased workload without appropriate reimbursement. The cost issue of RM of CIEDs is a controversial subject . Some regional studies in individual countries have shown that the RM of patients with CIEDs is a cost savings .…”
Section: Discussionmentioning
confidence: 99%
“…This, however, has been achieved at the expense of an increased workload without appropriate reimbursement. The cost issue of RM of CIEDs is a controversial subject . Some regional studies in individual countries have shown that the RM of patients with CIEDs is a cost savings .…”
Section: Discussionmentioning
confidence: 99%
“…In the few studies of patient satisfaction that are available, a number of studies 28,38 have reported no difference in the quality of life and patient satisfaction when comparing remote and conventional follow-up strategies. Other authors 21,36,39,40 have reported a high rate of patient satisfaction for diverse aspects such as patient's perceived relationship with their health care providers, ease of use, psychological impact, and the ability to maintain follow-up compliance, even with nonwireless transceivers.…”
Section: Patient Satisfaction and Quality Of Lifementioning
confidence: 99%
“…Early small studies based on cost estimates or models based on review of the literature suggested this was indeed the case, and this has recently been substantiated in a prospective study based on actual costs. 38,89 The ECOST study evaluated 310 patients randomly assigned to RM (plus 1 annual visit, unless RM dictated otherwise) vs outpatient follow-ups every 6 months. Costs within the French health insurance system were evaluated and included outpatient visits and transportation , 2217 2218 2219 2220 2221 2222 2223 2224 2225 2226 2227 2228 2229 2230 2231 2232 2233 2234 2235 2236 2237 2238 2239 2240 2241 2242 2243 2244 2245 2246 2247 2248 2249 2250 2251 2252 2253 2254 2255 2256 2257 2258 2259 2260 2261 2262 2263 2264 2265 2266 2267 2268 2269 2270 2271 2272 2273 2274 2275 2276 2277 2278 2279 ...…”
Section: Section 6: Reimbursement Legal and Privacy Considerations mentioning
confidence: 99%
“…(39, 40) In the former case, cost savings of €315 per patient year were accrued to the French healthcare system in patients randomized to RM versus usual care (p=0.05). In EVOLVO, RM proved to be cost-effective within the Italian healthcare system with savings of €888.10 per patient.…”
Section: Cost Effectivenessmentioning
confidence: 99%